Representative volume element size for accurate solid oxide fuel cell cathode reconstructions from focused ion beam tomography data - Joos, Jochen; Ender, Moses Johannes; Carraro, Thomas; Ivers-Tiffée, Ellen (Electrochimica acta, 2012)
Electrode performance in solid oxide fuel cells is strongly affected by its microstructure characteristics. A three-dimensional reconstruction of a mixed-conducting La0.58Sr0.4Co0.2Fe0.8O3−δ (LSCF)-cathode is introduced, which gives a detailed description thereof. At first, the multistep procedure of FIB/SEM (focused ion beam/scanning electron microscopy) tomography is analyzed, error sources are identified and measures taken against are presented. Special emphasis is turned on adequate SEM image resolution, on representative volume elements essential for trustworthy results and on important aspects of the numerical simulation. Our corrected reconstruction data set represents a volume of ∼2800μm3 and contains ∼96×106voxels. This data set is then used for calculating: (i) volume-specific surface area of the LSCF cathode, (ii) volume/porosity fraction, and (iii) tortuosity of LSCF and pores at a constant base area, but for an increasing height of the reconstructed electrode. Moreover, the course of these microstructure parameters is calculated independently for three representative volume elements.